Reconsidering Summer School of the International Camp Stojan Janković Castle (2006, 2007, 2008) - Miščević, Ljubomir (2008)
An on-going experience, related to the organization of international work camps and summer schools in Stojan Janković Castle in Islam Grčki (Zadar County, Croatia), in cooperation with partners from Belgium and France for the last three years (2006, 2007, 2008) has been reconsidered. The reconstruction of the Castle, heavily demaged in the war 1991-1995, brings together the idea of revitalization and international communication, based on interculturalism, culture of peace and toleration. A project of an Interuniversity Center has been already launched and supported by universities in Zagreb and Zadar.